EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DAN PENGELOMPOKKAN SAMPAH DI SD ISLAM INSAN UNGGUL KOTA KENDARI, PROVINSI SULAWESI TENGGARA - Henny Kasmawati; Suryani Suryani; La Ode Muhammad Fitrawan; Nurull Hikmah; Nurramadhani A. Sida; Ruslin Ruslin; Aswani Aswani (Jurnal Pengabdian NUSANTARA, 2022)
In order to accelerate recovery after the Covid-19 pandemic, especially in Kendari, South East Sulawesi, it is necessary to understand and be aware of the importance of maintaining health which starts with a healthy clean-living behaviour (PHBS) which starts from an early understanding of doing PHBS in elementary schools (SD).  Important indicators that become critical in this activity are how to wash hands well and group organic and inorganic waste. This activity is also a manifestation of the President's vision for 2020-2024 through the Ministry of Health to improve public health. This community service aims to increase public understanding and awareness, especially students of SD Islam Insan Unggul Kendari about the importance of carrying out healthy clean-living behaviour (PHBS). The method used is education by showing PHBS videos and socialization followed by interactive quizzes. This activity was easily well received by the participants because it used a learning-by-play approach so that the participants were easier to remember and apply in everyday life.